1999
DOI: 10.1086/303274
|View full text |Cite
|
Sign up to set email alerts
|

Density‐Dependent Variation in Lifetime Breeding Success and Natural and Sexual Selection in Soay Rams

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org..

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
137
2

Year Published

2001
2001
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(153 citation statements)
references
References 51 publications
14
137
2
Order By: Relevance
“…This value is much lower than the one typically observed in species with female defense systems in which a few males monopolize the access to females. For example, in the highly polygynous and sexually dimorphic northern elephant seal (Mirounga angustirostris), Soay sheep (Ovis aries), and bighorn sheep (Ovis canadensis), the average Is value for males were 21.8, 3.5, and 4.5, respectively (Le Boeuf and Reiter 1988;Coltman et al 1999Coltman et al , 2002. The Is values that we observed are in the order of those reported for other squirrel species.…”
Section: Discussionsupporting
confidence: 63%
“…This value is much lower than the one typically observed in species with female defense systems in which a few males monopolize the access to females. For example, in the highly polygynous and sexually dimorphic northern elephant seal (Mirounga angustirostris), Soay sheep (Ovis aries), and bighorn sheep (Ovis canadensis), the average Is value for males were 21.8, 3.5, and 4.5, respectively (Le Boeuf and Reiter 1988;Coltman et al 1999Coltman et al , 2002. The Is values that we observed are in the order of those reported for other squirrel species.…”
Section: Discussionsupporting
confidence: 63%
“…However, this project opens the way to the more challenging task of detecting QTL affecting a variety of morphological and physiological traits. The Soay sheep has been the subject of a number of studies aimed at estimating quantitative genetic parameters for traits like birth weight and body size (Coltman et al 1999;Milner et al 2000Milner et al , 2004. It has been found that the additive genetic variance of these traits is low but not null, despite the pressure of selection acting on them (Milner et al 2000).…”
Section: Mapping Ofmentioning
confidence: 99%
“…Although Nunney's (1993) model accounts for the potential disparity between seasonal and lifetime variance in reproductive success (provided that sex ratio is estimated in an appropriate manner), the use of cross-sectional data may be biased if there is substantial interannual variation in mating patterns. For example, long-term studies of free-ranging red deer (Cervus elaphus) and Soay sheep (Ovis aries) have demonstrated cohort-specific effects on male reproductive success as a result of environmental and demographic variation in the year of birth (Pemberton et al 1996(Pemberton et al , 1999Clutton-Brock et al 1997;Rose et al 1998;Coltman et al 1999b).…”
Section: /Nmentioning
confidence: 99%